2023
DOI: 10.1038/s41389-023-00464-4
|View full text |Cite
|
Sign up to set email alerts
|

The p52-ZER6/G6PD axis alters aerobic glycolysis and promotes tumor progression by activating the pentose phosphate pathway

Abstract: Abnormal glucose metabolism is a highlight of tumor metabolic reprogramming and is closely related to the development of malignancies. p52-ZER6, a C2H2-type zinc finger protein, promotes cell proliferation and tumorigenesis. However, its role in the regulation of biological and pathological functions remains poorly understood. Here, we examined the role of p52-ZER6 in tumor cell metabolic reprogramming. Specifically, we demonstrated that p52-ZER6 promotes tumor glucose metabolic reprogramming by positively reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Moreover, enhanced dimerization of G6PD, either through a knockdown of factors that inhibit G6PD dimerization, such as p53 and Bcl-2-associated athanogene 3 (BAG3) [67,118], or through overexpression of factors that promote G6PD dimerization, such as PLK1 [83], can also enhance G6PD/PPP. Meanwhile, inhibition of G6PD/PPP through G6PD knockdown results in decreased tumor cell proliferation [20,21,75,78]. These studies underscore that G6PD, through its role in counteracting ROS imbalance, helps cells avoid cell cycle arrest and enhances proliferation.…”
Section: Role Of G6pd In Tumor Cell Proliferationmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, enhanced dimerization of G6PD, either through a knockdown of factors that inhibit G6PD dimerization, such as p53 and Bcl-2-associated athanogene 3 (BAG3) [67,118], or through overexpression of factors that promote G6PD dimerization, such as PLK1 [83], can also enhance G6PD/PPP. Meanwhile, inhibition of G6PD/PPP through G6PD knockdown results in decreased tumor cell proliferation [20,21,75,78]. These studies underscore that G6PD, through its role in counteracting ROS imbalance, helps cells avoid cell cycle arrest and enhances proliferation.…”
Section: Role Of G6pd In Tumor Cell Proliferationmentioning
confidence: 86%
“…G6PD upregulation in tumor cells enhances their anti-oxidant activity, helping in the maintenance of ROS balance, preventing cell cycle arrest, and enhancing proliferation [10,124]. Our previous findings demonstrated that positive regulation of G6PD transcriptional activity by various transcription factors (including YY1, NeuroD1, PBX3, and p52-ZER6) enhances tumor cell proliferation by promoting tumor cell nucleotides and lipid biosynthesis [20,21,75,78].…”
Section: Role Of G6pd In Tumor Cell Proliferationmentioning
confidence: 97%
See 1 more Smart Citation
“…Under normal physiological conditions, regulatory factors involved in tumour occurrence and development are inactive, and some KRAB-ZNFs participate in negative regulation of these factors. In the process of tumour occurrence and further development influenced by external factors, some KRAB-ZNFs could also play a negative role in tumour occurrence and development 16 - 17 . It has been found that members of the KRAB-ZNF family play an important role in RCC, a finding helpful for obtaining a better understanding of the molecular mechanism of RCC occurrence and searching for potential molecular markers for the diagnosis and treatment of RCC 18 .…”
Section: Introductionmentioning
confidence: 99%